Correlation between serum gamma glutamyl transferase with atherogenic index of plasma with angiographic severity in patients with coronary artery disease - Raveekumaran, Vignessh; Prasath, Arun; Masilamani, Sivasankar; Mary, Jenifer Florence (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide. Gamma-glutamyl transferase (GGT) has been found to be involved in the pathogenesis of CAD. The aim of the study was to study the correlation between serum GGT and the atherogenic index of plasma (AIP) with angiographic severity in patients with CAD. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. This was an analytical cross-sectional study performed in 150 CAD patients in a tertiary-care teaching hospital in Puducherry, India. The patients were categorized as ST-elevated myocardial infarction (STEMI), non-ST-elevated MI (NSTEMI) and unstable angina. Routine biomarkers including troponin-I, AIP, GGT, and angiographic severity were calculated by applying a Gensini score (GS). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. The mean age of the study participants was 55.7±10.2 years, predominantly males. The GGT and GS was higher in STEMI group followed by NSTEMI and unstable angina groups (p<0.001 and 0.016, respectively). This indicates that GGT could be a potential biomarker for CAD, specifically in STEMI. AIP was shown to be statistically significant in unstable angina patients (p=0.029). GGT and GS showed a positive correlation with each other, and were statistically significant (r=0.1685, p=0.0387). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. Elevated serum GGT levels were positively correlated with angiographic severity of CAD with stronger associations in patients who had STEMI.